2018
DOI: 10.1016/j.jvscit.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical treatment with ex vivo technique in a patient with renal artery aneurysm rupture and bilateral arteriovenous fistula

Abstract: Renal arteriovenous fistulas are pathologic communications between the renal arteries and veins without interconnecting capillaries. Reports on the combination of fibromuscular dysplasia, aneurysms, and renal arteriovenous fistula are extremely rare in the literature. In the case of renal arteriovenous aneurysm rupture, urgent nephrectomy was the only life-saving procedure reported. The ex vivo approach seems to be an appropriate alternative to nephrectomy. This article presents a case of successful treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
1
Order By: Relevance
“…Our experimental morphological study is based on a 3D analysis of variants of the intra-organ division of the main branches of the renal arteries and the fusion of the main renal venous vessels. We have carried out studies to study the topographic and anatomical features of the structure of the arterial vessels of the kidneys relative to the venous vessels, since, according to some researchers, the renal veins repeat the course of the cognominal arteries [6][7][8][9][10][11][12][13][14][15][16][17][18][19], with which we cannot agree. The results of our studies revealed 17 topographic and anatomical variants of the location of the arteries relative to the venous vessels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our experimental morphological study is based on a 3D analysis of variants of the intra-organ division of the main branches of the renal arteries and the fusion of the main renal venous vessels. We have carried out studies to study the topographic and anatomical features of the structure of the arterial vessels of the kidneys relative to the venous vessels, since, according to some researchers, the renal veins repeat the course of the cognominal arteries [6][7][8][9][10][11][12][13][14][15][16][17][18][19], with which we cannot agree. The results of our studies revealed 17 topographic and anatomical variants of the location of the arteries relative to the venous vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, attempts have been made to clarify the anatomy and topography of the renal vessels using new means and methods [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Thus, some researchers confirm that the course of the intra-organ venous vessels of the kidneys largely coincides with the arterial ones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological role of these vessels is important in maintaining trophic and drainage functions where conditions such as hypertension and congestive kidney may develop in pathology [7][8][9][10]. According to some authors, when performing surgical interventions, information about the peculiarities of the blood supply to the kidney zones, the branching of the vascular basins in the organ parenchyma is very important, and information about the venous drainage of the organ is very important as well because metastases spread through these vessels from tumor foci [11][12][13]. The literature contains conflicting information about the structural features of these arteries and veins, their intra-organ branches, and the distribution of venous vessels [13].…”
Section: Introductionmentioning
confidence: 99%